An overview of anoxygenic phototrophic bacteria and their applications in environmental biotechnology for sustainable Resource recovery - Drishya M. George (17058075) (2020)
Anoxygenic phototrophic bacteria (APB) are a phylogenetically diverse group of organisms that can harness solar energy for their growth and metabolism. These bacteria vary broadly in terms of their metabolism as well as the composition of their photosynthetic apparatus. Unlike oxygenic phototrophic bacteria such as algae and cyanobacteria, APB can use both organic and inorganic electron donors for light-dependent fixation of carbon dioxide without generating oxygen. Their versatile metabolism, ability to adapt in extreme conditions, low maintenance cost and high biomass yield make APB ideal for wastewater treatment, resource recovery and in the production of high value substances. This review highlights the advantages of APB over algae and cyanobacteria, and their applications in photo-bioelectrochemical systems, production of poly-β-hydroxyalkanoates, single-cell protein, biofertilizers and pigments. The ecology of ABP, their distinguishing factors, various physiochemical parameters governing the production of high-value substances and future directions of APB utilization are also discussed. Other Information Published in: Biotechnology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.btre.2020.e00563 Additional institutions affiliated with: Biological Sciences Program - CMU-Q